(untitled) (Stato, Chiese e pluralismo confessionale, 2017)
SOMMARIO: 1. Il matrimonio nella teologia ortodossa - 2. I caratteri essenziali del matrimonio ortodosso - 3. Il principio di oἰκονομία - 4. Oἰκονομία e indissolubilità del matrimonio. Divorce and oikonomia in Orthodox canon law: the merciful application of the law ABSTRACT: Despite the fact that the principles of the unity and indissolubility of the conjugal bond represent constituent and essential properties of the sacrament of marriage in Eastern law, Orthodox theology allows some exceptions due to the schlerocardia of man, permitting the “economic” application of the rule. The paper aims to outline the ontological essence of oikonomia as a transposition in the human dimension of the redeeming force of the divine condescension. According to tradition, the institution finds its privileged application in marriage; therefore, the intention is to demonstrate that Orthodox ecclesiology tolerates second marriages as the “lesser evil” compared to fornication. This applies both to second marriages of divorcees and widows/widowers, since the sacrament of marriage survives the physical death of the spouse and remains a real image of the Mystery of the Incarnation. The paper will then analyse the circumstances that justify the “economic” interpretation of the precept: the “moral death” of the marriage due to a serious and despicable act, collective good, the worse damage that could derive from the rigid interpretation of the rule (akribeia)